2008
DOI: 10.1016/j.fct.2008.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological characterization of table olives commercialized in Portugal in respect to safety aspects

Abstract: a b s t r a c t Table olives are a traditional component of the Mediterranean diet and are largely consumed in the world. There are different trade treatments that originate different types of olives. The aim of the present work was to proceed to the microbiological characterization of table olives commercialized in the Portuguese market, with respect to their microbiological safety. The microbiological characterization was made in the olive pulp and packing brine of thirty-five table olives samples of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 20 publications
6
22
0
Order By: Relevance
“…Similar results have been reported by others authors (Randazzo et al 2002). In a recent study carried out on table olives commercialized in Portugal, Pereira et al (2008) reported a distribution of microbial population between pulp and brine similar to that , the combination of a high NaCl concentration in fresh brine at the beginning of fermentation beside a high total polyphenol as evaluated at the end of fermentation (e.g. see sample C5, Table 1, 5), seems not inhibit the growth of lactobacilli (Table 2).…”
Section: Microbiological Composition and Physicochemical Analysessupporting
confidence: 91%
“…Similar results have been reported by others authors (Randazzo et al 2002). In a recent study carried out on table olives commercialized in Portugal, Pereira et al (2008) reported a distribution of microbial population between pulp and brine similar to that , the combination of a high NaCl concentration in fresh brine at the beginning of fermentation beside a high total polyphenol as evaluated at the end of fermentation (e.g. see sample C5, Table 1, 5), seems not inhibit the growth of lactobacilli (Table 2).…”
Section: Microbiological Composition and Physicochemical Analysessupporting
confidence: 91%
“…Diverse authors have studied the survival and determined the presence of pathogenic bacteria (Escherichia coli, Listeria monocytogenes, Staphylococcus aureus and Salmonella sp.) in diverse table olive trade preparations (Spyropoulou et al, 2001;Caggia et al, 2004;Pereira et al, 2008;RASFF portal 2012a;Argyri et al, 2013;Grounta et al, 2013;Medina et al, 2013;Tataridou and Kotzekidou, 2015). Botulism, associated with Clostridium botulinum growth, is certainly the most relevant biohazard in table olives with several reported outbreaks (Debord et al, 1920;Fenicia et al, 1992;Cawthorne et al, 2005;Jalava et al, 2011;Pingeon et al, 2011;RASFF portal 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Clostridial bacteria are relatively common in the environment because they are spore-forming. Spores of C. botulinum were detected both in pasteurized and sterilized olives (Pereira et al, 2008) indicating a poor attention to the application of sterilisation parameters. The occurrence of C. botulinum appears, however, to be rare.…”
Section: The Microbiological Hazards In Table Olivesmentioning
confidence: 99%
“…However, the Standards of the Codex Alimentarius prescribes the minimum requirements related to hygiene for table olives. The final product shall be free from microorganisms and parasites in amounts which may represent a hazard to health and shall not contain any substance originating from microorganisms in amounts which may represent a hazard to health (Pereira et al, 2008). To reduce the risk of food-borne illness and spoilage phenomenon, good practices in agriculture (GAP), hygiene (GHP) and manufacturing (GMP) must be applied.…”
Section: The Microbiological Hazards In Table Olivesmentioning
confidence: 99%